Implementation of Hospital Risk Management Using Bowtie Method - Azkadini Rachmawati; Tatan Sukwika; Soehatman Ramli (Institute of Computer Science (IOCS), 2022)
Every hospital is required to have risk management to prevent adverse events when providing health services. The application of risk management in hospitals helps identify and control incidents of work accidents that occur in hospitals, especially in the General Affairs and Engineering sections of the Hospital. The purpose of this research is to identify the source of the cause, impact, and control of the dominant occupational accident risk during work activities in the general affairs and engineering section of the hospital. Analysis with qualitative methods using data from observations and questionnaires. The results of the study found that there were two most dominant risks, namely medical waste management and MEP work on electric voltage hazards. It was concluded that there was a match between the application of risk management by the hospital and the results of testing the Bowtie method. Suggestions for this research are to review the risk assessment in height work, as well as to supervise the work methods carried out by workers.